2012
DOI: 10.1002/biot.201100475
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput process development of chromatography steps: Advantages and limitations of different formats used

Abstract: In the past, development of a chromatographic separation method has been accomplished by performing a series of experiments using either manual or automated chromatography systems. The screening of a vast experimental space became very expensive because all experiments had to be performed in a serial manner, and the chromatography systems used were designed for relatively large columns and, therefore, the experiments required large sample volumes. To address these issues, high-throughput miniaturized methods e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…In recent years, significant advances have been made in the determination of protein binding as a function of protein concentration and mobile phase composition over broad ranges of conditions both by using analytical tools that allow measurements with very low sample volumes as well as by implementing automated, high throughput screening (HTS) approaches [18][19][20][21]. While these approaches can generate large amounts of data, the quantitative connection between the data and column performance is not always straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant advances have been made in the determination of protein binding as a function of protein concentration and mobile phase composition over broad ranges of conditions both by using analytical tools that allow measurements with very low sample volumes as well as by implementing automated, high throughput screening (HTS) approaches [18][19][20][21]. While these approaches can generate large amounts of data, the quantitative connection between the data and column performance is not always straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…For linear adsorption isotherms, or cases where uptake is expected to be enhanced by homogeneous diffusion of bound protein, the assumption of bound protein remaining in place on the surface between steps may no longer be appropriate. For systems exhibiting very rapid diffusivity, two challenges may be encountered: achieving sufficiently-rapid external mass transfer from the fluid to the particle surface within the microplate environment [18,42] and the intrinsic time scales involved in performing protein addition, incubation, and separation steps on a high-throughput system. If equilibrium is reached before separation may be performed in a given step, only a lower limit on diffusion rates will be extractable from the collected data.…”
Section: Variablementioning
confidence: 99%
“…Further, the incubation time was significantly greater than the dead time between incubation and protein separation and re-addition. Analysis of the Biot number performed by Lacki [42] for mAb uptake in an agitated micro-plate on a macroporous ion exchange resin suggests that external mass transfer is sufficiently-capable of delivering protein to the particle surface (Bi = 10 2 ) based on an effective diffusivity to free solution diffusivity ratio (D e /D 0 ) of 0.1.…”
Section: Variablementioning
confidence: 99%
“…Specifically for small proteins, it has been reported that velocity‐dependent mass transfer becomes the rate‐limiting step, limiting the ability for miniature columns to be predictive of higher capacity purification schemes. However, it is also noted for preparative applications, velocities typically fall well within the range to be predictive of higher capacity purification schemes . Additional concerns reported to impact the predictive capabilities of miniature columns include geometric factors, including bed volume heights leading to reduced separation capacities, residence times and flow rates, “wall effects” from a smaller inner‐diameter, and nonlinear elution gradients.…”
Section: Introductionmentioning
confidence: 98%